(3fXe GdaUjMs - (3YHO GdMejO Hf gHI Gddg Hf eMeO Hf GdMSjf , GHf CHj GdMOjO , YR GdOjf CHh MGeO,J (B656 (3g` s ((3fUQ Hf eMeO Hf fUQ GdLYHQi GdHYdHci s)
(3ChdgG (B:s
(3jbhd QGLi QHg GdMejO YHOG dMejO Hf CHj GdMOjO CHOC HGdMeO dPi GdeMGeO GdMGce GdYOd GdEdg GdhGMO hbO fXeJ dZI GdaUjM dKYdH ai QLR eTQhM s
(3BNQgG (B:s
(3hGdMeO ddg Ydi EJeGeI caGAI eG CSOGg ef EfYeGeg dg QLGFi hHg EYJUGei Ke Ydi fHjg SdGei Je fXe GdaUjM s
(3GdfSNI HgG MhGTs
(3YdjgG JbjjOGJs
(3eG cGf efgG Ydjg UhQI b agh ef cJGH GdJfHjg Ydi eG ai GdaUjM ef GdZdX dYdi Hf MeRI GdHUQis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs